1970
DOI: 10.1136/gut.11.3.250
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal absorption of carnosine and its constituent amino acids in man

Abstract: S U M MARY Serum concentrations of ,B-alanine and L-histidine are compared in five normal adults after ingestion of the dipeptide carnosine (/-alanyl-L-histidine) and after equivalent amounts of the constituent free amino acids. The results indicate that absorption is significantly more rapid after the ingestion ofthe amino acids than after the dipeptide. The use of the test in a case of Hartnup disease suggests that carnosine is taken up by intestinal cells as the dipeptide, but subsequent hydrolysis and deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0
7

Year Published

1972
1972
2012
2012

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 15 publications
7
29
0
7
Order By: Relevance
“…No adverse effects were caused by carnosine ingestion although some subjects experienced mild and transient digital paraesthesia within the first hour, a similar effect having been reported by Asatoor, Bandoh, Lant, Milne & Navab (1970). Figure 1 shows the urinary content of carnosine over the first 5 h after ingestion of 4 g of carnosine by six subjects.…”
Section: Urinary Output Of Carnosinesupporting
confidence: 56%
See 1 more Smart Citation
“…No adverse effects were caused by carnosine ingestion although some subjects experienced mild and transient digital paraesthesia within the first hour, a similar effect having been reported by Asatoor, Bandoh, Lant, Milne & Navab (1970). Figure 1 shows the urinary content of carnosine over the first 5 h after ingestion of 4 g of carnosine by six subjects.…”
Section: Urinary Output Of Carnosinesupporting
confidence: 56%
“…The presence of such effective carnosinase activity in plasma explains why Asatoor et al (1970) and Sadikali et at. (1975) failed to detect carnosine in plasma after carnosine ingestion by humans.…”
Section: Discussionmentioning
confidence: 99%
“…As Gardner et al reported, no adverse effects were observed aside from a mild and transient digital paraesthesia that some subjects experienced within the first hour. Paraesthesia occurring from about 15-45 min after the ingestion of *2.5 g of carnosine (0.286 mmol/kg body weight) was also reported by Asatoor et al (1970).…”
Section: Negative Side Effectsmentioning
confidence: 61%
“…Initial attempts to measure plasma levels of carnosine in human probands have not yielded reliable data (Asatoor et al 1970); it was shown that ex vivo hydrolysis during blood collection resulted in an apparent half-life of carnosine of the order of 1 min (Gardner et al 1991). Although this does not reflect carnosine's biological halflife in serum, the fact that urinary recovery of carnosine is possible by the fourth hour after ingestion poses a question to the fate of absorbed carnosine before excretion.…”
Section: Plasma Levels Of Carnosinementioning
confidence: 99%
“…These findings are in accordance with the earlier in vivo and in vitro studies (Scriver, Pueschel & Davies, 1966;Goldman & Scriver, 1967;Nutzenadel & Scriver, 1976;Dantzler & Silbernagl, 1976) which indicated that in the kidney ,-amino acids share a common transport system which is different from that for oc-amino acids. In addition to the kidney, a transport system specific for f-amino acids was reported in intestine (Asatoor, Bandoh, Lant, Milne & Navab, 1970) and in Ehrlich ascite tumour cells (Christensen, 1964 …”
Section: Discussionmentioning
confidence: 99%